Tuberosity Repair in Reverse Total Shoulder Arthroplasty for Fracture Using a Stem-based Double-row Repair: A Cadaveric Biomechanical Study. Issue 23 (1st December 2020) - Erickson, Brandon J.; Shishani, Yousef; Bishop, Meghan E.; Romeo, Anthony A.; Lederman, Evan; Gobezie, Reuben
Abstract : Introduction: The optimal tuberosity repair method in reverse total shoulder arthroplasty for fracture is unknown. Methods: Eight matched pairs of cadaver shoulders were randomly assigned to a stem-based tuberosity repair technique or a nonstem-based repair (Boileau technique) and mechanically tested with a 10 kN load cell. Cyclic loading was performed between 10 and 100 N for 500 cycles at 1 Hz, followed by static pull to failure at 33 mm/s. Ultimate load was determined from the maximum load reached during the pull to failure. A paired Student t -test was used to compare the means of the ultimate load and average cyclic displacement of the two sample groups. Results: The ultimate load to failure for the stem-based tuberosity repair technique was significantly higher than the nonstem-based technique (668 ± 164 N versus 483 ± 67 N; P = 0.032). The average cyclic displacement for the stem-based tuberosity repair technique was significantly less than the nonstem-based technique 0 (0.83 ± 0.67 mm versus 3.36 ± 2.36 mm; P = 0.017). Conclusion: The stem-based tuberosity repair technique afforded higher ultimate load to failure with less average cyclic displacement than the nonstem-based technique. Consideration to the stem-based technique should be given when performing a tuberosity repair in the setting of reverse total shoulder arthroplasty for fracture. Level of Evidence: Level III